Applied machine learning and AI for engineers : solve business problems that can't be solved algorithmically - Prosise, Jeff; Prosise, Adam (Sebastopol, CA : O'Reilly Media, 2023)
While many introductory guides to AI are calculus books in disguise, this one mostly eschews the math. Instead, author Jeff Prosise helps engineers and software developers build an intuitive understanding of AI to solve business problems. Need to create a system to detect the sounds of illegal logging in the rainforest, analyze text for sentiment, or predict early failures in rotating machinery? This practical book teaches you the skills necessary to put AI and machine learning to work at your company.
Includes bibliographical references and index.
Keywords: Machine learning; Artificial intelligence